2011
DOI: 10.1167/iovs.11-7587
|View full text |Cite
|
Sign up to set email alerts
|

Role of TGFβ/Smad Signaling in Gremlin Induction of Human Trabecular Meshwork Extracellular Matrix Proteins

Abstract: Gremlin employs canonical TGFβ2/Smad signaling to induce ECM genes and proteins in cultured human TM cells. Gremlin also induces both TGFβ2 and CTGF, which can act downstream to mediate some of these ECM changes in TM cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
94
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(96 citation statements)
references
References 45 publications
2
94
0
Order By: Relevance
“…Transforming growth factor-1 (TGF 1) is the most potent cytokine that can promote the activation of HSCs, and gremlin is a downstream molecule of TGF-. There is evidence showing that TGF-1 can specifically increase the protein and mRNA expression of gremlin, which has been found to be related to the fibrosis (Sethi et al, 2011). Thus, to block the above targets to inhibit the fibrosis is of great importance in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Transforming growth factor-1 (TGF 1) is the most potent cytokine that can promote the activation of HSCs, and gremlin is a downstream molecule of TGF-. There is evidence showing that TGF-1 can specifically increase the protein and mRNA expression of gremlin, which has been found to be related to the fibrosis (Sethi et al, 2011). Thus, to block the above targets to inhibit the fibrosis is of great importance in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Gremlin also elevates IOP in perfusion-cultured human anterior segments. 5,9 Here, we demonstrate that gremlin induces ocular hypertension and alters the ECM composition in the TM of mice. We also show that gremlin signaling through the canonical Smad pathway is essential for this gremlin-induced ocular hypertension.…”
mentioning
confidence: 66%
“…9 We have also shown that gremlin alone can induce these ECM proteins in TM cells. 5 The TM is a key tissue in IOP regulation. Therefore, we determined the effect of gremlin overexpression on IOP in mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26][27][28] A great deal of effort has gone into exploring how these different bioactive agents influence TM tissue properties and cell biology in the context of AH outflow in both in vitro and in vivo studies. 15,16,24,[29][30][31][32][33][34][35][36] These efforts are beginning to unravel the participation of several different intracellular signaling mechanisms, including Rho GTPase, Wnt, ECM/ mechanotransduction, integrins, nitric oxide, PKC, BMPs/ SMADs, MAP kinases, and others, in regulating contractile properties of TM cells, ECM turnover, adhesive interactions, biomechanical properties, permeability, and survival of outflow pathway tissues and cells. 14,24,[37][38][39][40] These different observations offer significant insights into the regulation of AH outflow and suggest several novel avenues to target selected signaling pathways and other molecular targets for increasing AH outflow through the conventional pathway, and for the development of new and mechanism-based IOP lowering drugs.…”
Section: Introductionmentioning
confidence: 99%